2002
DOI: 10.1093/emboj/cdf441
|View full text |Cite
|
Sign up to set email alerts
|

Caspase-10 is recruited to and activated at the native TRAIL and CD95 death-inducing signalling complexes in a FADD-dependent manner but can not functionally substitute caspase-8

Abstract: The involvement of the death adaptor protein FADD and the apoptosis-initiating caspase-8 in CD95 and TRAIL death signalling has recently been demonstrated by the analysis of the native death-inducing signalling complex (DISC) that forms upon ligand-induced receptor cross-linking. However, the role of caspase-10, the other death-effector-domain-containing caspase besides caspase-8, in death receptor signalling has been controversial. Here we show that caspase-10 is recruited not only to the native TRAIL DISC bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
240
1
5

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 321 publications
(269 citation statements)
references
References 32 publications
17
240
1
5
Order By: Relevance
“…P693 cells were injected subcutaneously into nude mice to generate tumor xenografts. After 2 days, tumor nodules of approximately 50 mm 3 were detectable consisting of about 1-2 Â 10 7 cells (data not shown). Ten mice per group were injected with vehicle (PBS/BSA), LV-GFP or LV-TRAIL (1.5 Â 10 7 IU in 50 ml PBS/BSA) directly into the tumor, resulting in a MOI of approximately 1.…”
Section: Transient Growth Retardation Of Established Tumors By Lv-tramentioning
confidence: 85%
See 2 more Smart Citations
“…P693 cells were injected subcutaneously into nude mice to generate tumor xenografts. After 2 days, tumor nodules of approximately 50 mm 3 were detectable consisting of about 1-2 Â 10 7 cells (data not shown). Ten mice per group were injected with vehicle (PBS/BSA), LV-GFP or LV-TRAIL (1.5 Â 10 7 IU in 50 ml PBS/BSA) directly into the tumor, resulting in a MOI of approximately 1.…”
Section: Transient Growth Retardation Of Established Tumors By Lv-tramentioning
confidence: 85%
“…FLAG-TRAIL and TRAIL-R2-Fc protein have been described. 3,27 All other chemicals were from Sigma or Carl Roth (Karlsruhe, Germany).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…While it is known that caspase-8 and -10 are cleaved in the same manner, the importance of caspase-10 to the DISC is still the subject of controversy (Kischkel et al, 2001). One study has shown that its expression can restore apoptosis sensitivity to caspase-8-deficient cells, while another has shown the opposite (Sprick et al, 2002). It is known, though, that through the DISC, caspase-8 is autocatalytically cleaved, generating a large and a small subunit.…”
Section: Trail: Generalmentioning
confidence: 99%
“…Of these, some have TRAIL has also been combined with proteasome inhibitors to induce apoptosis (Sprick et al, 2002). It is believed that their combinatorial effect is achieved through TRAIL expression on NK cells, though this does not completely explain the increased sensitivity (Hallett et al, 2008).…”
Section: Trail and Cancer Treatmentmentioning
confidence: 99%